Assessing Anosognosia in Apraxia of Common Tool-Use With the VATA-NAT - Buchmann, Ilka; Jung, Rebecca; Liepert, Joachim; Randerath, Jennifer (Frontiers in Human Neuroscience, 2018)
In neurological patients, a lack of insight into their impairments can lead to possibly dangerous situations and non-compliance in rehabilitation therapy with worse rehabilitation outcomes as a result. This so called anosognosia is a multifaceted syndrome that can occur after brain damage affecting different neurological or cognitive functions. To our knowledge no study has investigated anosognosia for apraxia of common tool-use (CTU) so far. CTU-apraxia is a disorder frequently occurring after stroke that affects the use of familiar objects. Here, we introduce a new questionnaire to diagnose anosognosia for CTU-apraxia, the Visual Analogue Test assessing Anosognosia for Naturalistic Action Tasks (VATA-NAT). This assessment is adapted from a series of VATA-questionnaires that evaluate insight into motor (VATA-M) or language (VATA-L) impairment and take known challenges such as aphasia into account. 51 subacute stroke patients with left (LBD) or right (RBD) brain damage were investigated including patients with and without CTU-apraxia. Patients were assessed with the VATA-L, -M and -NAT before and after applying a diagnostics session for each function. Interrater reliability, composite reliability as well as convergent and divergent validity were evaluated for the VATA-NAT. Seven percent of the LBD patients with CTU-apraxia demonstrated anosognosia. After tool-use diagnostics this number increased to 20 percent. For the VATA-NAT, psychometric data revealed high interrater-reliability (τ ≥ .828), composite reliability (CR ≥ .809) and convergent validity (τ = -.626). When assessing patients with severe aphasia, the possible influence of language comprehension difficulties needs to be taken into account for interpretation. Interestingly, for all three VATA versions the retests resulted in an increased frequency of diagnosed anosognosia in the respective function despite having been confronted with the respective impairment during a diagnostic session. Future research may have to reveal which factors influence the presence or absence of anosognosia over time. Overall, close monitoring of anosognosia over the course of rehabilitation is recommended. With the VATA-NAT we hereby provide a novel assessment for anosognosia in patients with CTU-apraxia. For diagnosing anosognosia we recommend to combine this new tool with the existing VATA-M and -L subtests, particularly in patients who demonstrate severe functional deficits.